2015
DOI: 10.1080/02602938.2015.1048185
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peer assessment on project performance of students at different learning levels

Abstract: Peer assessment has been increasingly integrated in educational settings as a strategy to foster student learning. Yet little has been studied about how students at different learning levels may benefit from peer assessment. This study examined how peer assessment and students' learning levels influenced students' project performance by using a two-way factorial design. One hundred and thirty teacher education students participated in this quasi-experimental study. When working on a technology-integrated lesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 35 publications
1
34
0
3
Order By: Relevance
“…Whilst this may be a simple reflection of the more conscientious, able and engaged students spending longer on the task, if we consider the performance on the MCQ part of the examination a 'control' (in terms of a measure of knowledge not requiring skills in description of diagnostic/therapeutic approach), then this suggests that the benefit was more of a direct relation to time spent improving their abilities in the short answer section of the examination. This is consistent with a study reported by Li and Gao, 12 who showed that students who conducted peer assessment performed significantly better than students who did not.…”
Section: Discussionsupporting
confidence: 92%
“…Whilst this may be a simple reflection of the more conscientious, able and engaged students spending longer on the task, if we consider the performance on the MCQ part of the examination a 'control' (in terms of a measure of knowledge not requiring skills in description of diagnostic/therapeutic approach), then this suggests that the benefit was more of a direct relation to time spent improving their abilities in the short answer section of the examination. This is consistent with a study reported by Li and Gao, 12 who showed that students who conducted peer assessment performed significantly better than students who did not.…”
Section: Discussionsupporting
confidence: 92%
“…While maintaining anonymity in paper-based peer assessment is never an easy task (Li and Gao 2015), the advancement of modern technology has greatly streamlined the process and made administration of anonymous peer assessment almost effortless. In a computerised system, data are distributed and automated by relational databases, in which students' identities can be easily protected.…”
Section: Anonymity In Peer Assessmentmentioning
confidence: 99%
“…Keywords: peer assessment; anonymity; student learning; student perceptions Overview of peer assessment Peer assessment, although existing in many variants, usually involves students providing feedback on other students' work for the purpose of either formative feedback or summative grading, or an integration of both (Li and Gao 2015). As an effective learning tool, formative peer assessment often engages students in both roles as assessor and assessee.…”
mentioning
confidence: 99%
“…Peer feedback did not show any statistical difference and was rated high in both the groups. As reported by Robinson (Li, L and Gao, F, 2016) this could be because some students feel uneasy and reluctant to assess their peers' work and 'marking could be easily affected by friendship, cheating, ego or low self-esteem'. Hence the rating is same for both the groups and consistently high (Driessen et.…”
Section: Discussionmentioning
confidence: 98%